The CRISPR-Associated Gene cas2 of Legionella pneumophila Is Required for Intracellular Infection of Amoebae - Gunderson, Felizza F. (American Society of Microbiology, 2013)
Recent studies have shown that the clustered regularly interspaced palindromic repeats (CRISPR) array and its associated (cas) genes can play a key role in bacterial immunity against phage and plasmids. Upon analysis of the Legionella pneumophila strain 130b chromosome, we detected a subtype II-B CRISPR-Cas locus that contains cas9, cas1, cas2, cas4, and an array with 60 repeats and 58 unique spacers. Reverse transcription (RT)-PCR analysis demonstrated that the entire CRISPR-Cas locus is expressed during 130b extracellular growth in both rich and minimal media as well as during intracellular infection of macrophages and aquatic amoebae. Quantitative reverse transcription-PCR (RT-PCR) further showed that the levels of cas transcripts, especially those of cas1 and cas2, are elevated during intracellular growth relative to exponential-phase growth in broth. Mutants lacking components of the CRISPR-Cas locus were made and found to grow normally in broth and on agar media. cas9, cas1, cas4, and CRISPR array mutants also grew normally in macrophages and amoebae. However, cas2 mutants, although they grew typically in macrophages, were significantly impaired for infection of both Hartmannella and Acanthamoeba species. A complemented cas2 mutant infected the amoebae at wild-type levels, confirming that cas2 is required for intracellular infection of these host cells.